2004
DOI: 10.1182/blood-2003-08-2815
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic cystitis after allogeneic hematopoietic stem cell transplantation: donor type matters

Abstract: Hemorrhagic cystitis (HC) remains a common complication of allogeneic blood and marrow transplantation. Previous analyses of risk factors for this complication were performed in heterogenous populations, with dissimilar diagnosis and conditioning regimens. We postulated that HC is more prevalent in matched unrelated donor (MUD) and unrelated cord blood (UCB) transplantations than in matched related donor (MRD) transplantations. We performed a retrospective study on 105 acute lymphocytic leukemia patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
5
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 35 publications
6
92
5
1
Order By: Relevance
“…[9][10][11][12] Other reported factors include GVHD, unrelated BM or cord blood transplants, radiation and exposure to BU. 1,[34][35][36] The Embolization treatment of hemorrhagic cystitis after HSCT Y Han et al immune reactions play an important role in the pathogeneses of LOHC, which may lead to the immune attack of the recipient urothelium, causing more damage than the simple toxic effects of chemotherapy or the cytopathic effects of viral infections. Initially, the toxicity to the uroepithelium and immunosuppression caused by the conditioning regimen provides suitable conditions for viral replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] Other reported factors include GVHD, unrelated BM or cord blood transplants, radiation and exposure to BU. 1,[34][35][36] The Embolization treatment of hemorrhagic cystitis after HSCT Y Han et al immune reactions play an important role in the pathogeneses of LOHC, which may lead to the immune attack of the recipient urothelium, causing more damage than the simple toxic effects of chemotherapy or the cytopathic effects of viral infections. Initially, the toxicity to the uroepithelium and immunosuppression caused by the conditioning regimen provides suitable conditions for viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic cystitis (HC) is recognized as a significant cause of morbidity and sometimes mortality in patients undergoing hematopoietic SCT (HSCT) [1][2][3] shows a clinical manifestation varying from microscopic hematuria to severe hemorrhage with obstructive renal failure. 4,5 Its reported incidence ranges from less than 10% to more than 70% due to the discrepancies in definition criteria and the types of transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding risk factors, different studies have shown several levels of risk but CBU remains the highest risk in the HSCT settings. 10,22 In our study, CBU transplantation is the most significant risk factor for BKV-HC with a 38% cumulative incidence. Another study has previously proposed a risk stratification combining the type of donor and the HLA matching with a cumulative incidence of BKV-HC among patients receiving CBU, unrelated donor, mismatched related donor and matched related donor of 40%, 40%, 30% and 16%, respectively.…”
Section: High Burden Of Bk Virus-associated Hemorrhagic Cystitis L Gimentioning
confidence: 99%
“…Another study has previously proposed a risk stratification combining the type of donor and the HLA matching with a cumulative incidence of BKV-HC among patients receiving CBU, unrelated donor, mismatched related donor and matched related donor of 40%, 40%, 30% and 16%, respectively. 22 Another issue is the role of HLA mismatching as a cofactor for BK viruria as previously shown. 15 Although we showed that HLA mismatching and unrelated donor are cofactors in univariate analysis, multivariate analysis did not confirm it as independent risk factors.…”
Section: High Burden Of Bk Virus-associated Hemorrhagic Cystitis L Gimentioning
confidence: 99%
See 1 more Smart Citation